Cart-Go : Robot Troli Otomatis Pembawa Barang Belanjaan di Supermarket - Ananda Dirgari Effendi; Alvina Septariyani Effendi; Adam Fahla; Rahmat Hidayat (Jurnal Komputer dan Elektro Sains, 2025)
Cart-Go is an automatic cart robot that can follow customers while shopping in supermarkets. This robot aims to improve customer comfort and shopping experience, as well as solve the problem of transporting and managing shopping goods. This paper explains the background, methods, results, and discussion of research conducted to design and test the Cart-Go system. This research uses ultrasonic and infrared sensors to detect the distance and angle of objects, as well as DC motors and servos to move the robot. The test results show that the robot can move according to the distance and direction of the object, although there are limitations in the detection angle. This paper also discusses the advantages and disadvantages of the system, as well as suggestions for further research. Thus further improvements and developments can be carried out to improve system performance and efficiency. Some suggestions for further research are to use other sensors that are more accurate and sensitive, such as cameras or lidars, to detect objects, use servo motors that are more stable and precise, and use batteries that are more durable and environmentally friendly.